Reduplikasi Morfemis dalam Novel-Novel Metropop karya Ilana Tan - Endriani, Gustia; Liusti, Siti Ainim (Persona: Kajian Bahasa dan Sastra, 2024)
The aim of this research is to describe the object under study, namely morphemic reduplication in Ilana Tan's Metropop novels entitled Sunshine Becomes You and Winter In Tokyo. This type of research is qualitative research using descriptive methods. The data used are words or sentences that contain word formations (reduplication) in the novels Sunshine Becomes YouandWinter In Tokyo. The data collection method and technique used is the listening and reading method using the note-taking technique. The results of this research are as follows. First, four types of morphemic reduplication were found, namely dwipurwa found in 7 data, dwilingga found in 151 data, dwilingga salin swara found in 8 data, and dwiwasana found in 105 data. Second, in the process of forming reduplication, there are patterns in the duplicated words which are related to their word class. The pattern of reduplication formation used in this research uses the word classes noun (N), verb (V), adjective (A), adverbial (Adv), pronoun (Pr), and numeralia (Num). Third, the meaning of morphemic reduplication found in this research, namely the meaning: (1) not different (no change in meaning), (2) uncertain goods/things, (3) considered, (4) various, ( 5) a lot, (6) strongly, (7) intensity, (8) many times, (9) indefinitely, (10) earnestly, (11) somewhat, (12) aimlessly, (13) unconditionally , (14) not serious, (15) less serious, (16) reciprocated, (17) certain, and (18) relaxed.